2021
DOI: 10.3390/cells10081941
|View full text |Cite
|
Sign up to set email alerts
|

May the Force Be with You (Or Not): The Immune System under Microgravity

Abstract: All terrestrial organisms have evolved and adapted to thrive under Earth’s gravitational force. Due to the increase of crewed space flights in recent years, it is vital to understand how the lack of gravitational forces affects organisms. It is known that astronauts who have been exposed to microgravity suffer from an array of pathological conditions including an impaired immune system, which is one of the most negatively affected by microgravity. However, at the cellular level a gap in knowledge exists, limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 158 publications
0
30
0
Order By: Relevance
“…It is now known that individual mammalian cells in culture are capable of responding to changes in gravitational forces. However, as recent reviews show, the form of responses is complex [ 1 , 2 , 3 , 4 , 5 ]. Cells respond to both hypergravity created by centrifugation [ 6 , 7 , 8 , 9 ] and microgravity (µG).…”
Section: Introductionmentioning
confidence: 99%
“…It is now known that individual mammalian cells in culture are capable of responding to changes in gravitational forces. However, as recent reviews show, the form of responses is complex [ 1 , 2 , 3 , 4 , 5 ]. Cells respond to both hypergravity created by centrifugation [ 6 , 7 , 8 , 9 ] and microgravity (µG).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about how the lack of gravity will affect the health of space travelers. It has been shown that spaceflight and microgravity conditions can cause adverse effects on the immune system, neurological function, and bone density [ 1 , 2 , 3 ]. Several in vitro and animal studies report problems such as skin irritation and impaired wound healing under microgravity conditions [ 4 , 5 , 6 , 7 , 8 , 9 ], suggesting that this process could also be altered in astronauts during spaceflight.…”
Section: Introductionmentioning
confidence: 99%
“…Other notable medical events were upper respiratory symptoms such as congestion, rhinitis and sneezing (0.97/flight year), followed by various other symptoms such as cold sores, ear problems, and infectious symptoms (>0.3/flight year). This increase in skin sensitivity, reported as rashes during flight, might be a consequence of a dysregulated immune system in microgravity [ 13 , 14 , 15 ]. Furthermore, increased skin sensitivity, skin thinning and delayed wound healing, as well as increased susceptibility for skin infections, have been reported [ 16 ].…”
Section: Current Knowledge On Spaceflight-induced Skin Health Effectsmentioning
confidence: 99%
“…As such, skincare related to cleaning and moisturizing, as well as reducing injuries obtained from hardware such as spacesuits, should be optimized. Furthermore, a dysregulation of the immune system in microgravity can further contribute to the symptoms of skin sensitivity and rashes, and can delay wound healing [ 13 , 14 , 15 , 96 ]. Therefore, better understanding of immune function during long-term spaceflight, and how this may contribute to observed skin sensitivity, is desirable.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%